Faktor-Faktor Kesulitan Mahasiswa Menyusun Skripsi Pada Prodi Penjaskesrek FKIP Universitas PGRI Mahadewa Indonesia di Era Adaptasi Kebiasaan Baru Tahun 2021 - N.W.A. Rusitayanti; N.W. Ariawati; N.L.P. Indrawathi; N.L.G Widiantari (Pascasarjana Universitas Pendidikan Ganesha, 2021)
This study aims to determine the difficulty factors of the Penjaskesrek Study Program students, FKIP, Universitas PGRI Mahadewa Indonesia when compiling a thesis in the era of adaptation of new habits in 2021. This research is included in a qualitative descriptive study, with a population of 47 students who take thesis courses in the semester. 8 academic years 2020/2021 and the research sample using the case study method was taken as many as 7 students who had not completed the thesis course in the 8th semester of the 2020/2021 academic year. The data collection technique is triangulation (combined), the data analysis is inductive/qualitative, and the results of qualitative research emphasize meaning rather than generalization. Based on the results of the study, it was found that the difficulty of writing a thesis in terms of internal factors, including health, motivation, busyness, ability to write thesis and time management. Meanwhile, from external factors, namely family, peers, thesis administration, references, and guidance methods in the era of adapting new habits. The dominant internal factors that affect the difficulty of thesis preparation are the busyness factor and the ability to write student thesis, while the dominant external factor influencing the preparation of student thesis is family factors, especially in terms of economics and online guidance in the era of adapting new habits.